Glutathione-s-transferase modified electrodes for detecting anticancer drugs - Materon, Elsa M. [UNESP]; Huang, Po-Jung Jimmy; Wong, Ademar [UNESP]; Pupim Ferreira, Antonio A. [UNESP]; Taboada Sotomayor, Maria Del Pilar [UNESP]; Liu, Juewen (Elsevier B.V., 2014)
With the fast growth of cancer research, new analytical methods are needed to measure anticancer drugs. This is usually accomplished by using sophisticated analytical instruments. Biosensors are attractive candidates for measuring anticancer drugs, but currently few biosensors can achieve this goal. In particular, it is challenging to have a general method to monitor various types of anticancer drugs with different structures. In this work, a biosensor was developed to detect anticancer drugs by modifying carbon paste electrodes with glutathione-s-transferase (GST) enzymes. GST is widely studied in the metabolism of xenobiotics and is a major contributing factor in resistance to anticancer drugs. The measurement of anticancer drugs is based on competition between 1-chloro-2,4-dinitrobenzene (CDNB) and the drugs for the GST enzyme in the electrochemical potential at 0.1 V vs. Ag/AgCl by square wave voltammetry (SWV) or using a colorimetric method. The sensor shows a detection limit of 8.8 mu M cisplatin and exhibits relatively long life time in daily measurements. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Glutathione-s-transferase; Carbon past electrode; Cisplatin; Glutathione